Acute suppurative thyroiditis in young children - Oranan Wongphyat (2018)
We report two children with acute suppurative thyroiditis (AST). They presented with typical features of AST, which include fever, painful goiter and biochemical euthyroidism. An anatomical defect predisposed to thyroid infection, pyriform sinus fistula, was identified in one patient. Both patients responded well to surgical pus drainage and antibiotic treatment. Anatomical defects must be sought in all children with AST to perform specific surgical treatment and prevent recurrent infection. © 2011 Paediatrics and Child Health Division (Royal Australasian College of Physicians).